Cyclic strain sweep testing-analysis to evaluate the mechanical characteristics of stabilized soils. (March 2023) - Kommidi, Santosh Reddy; Akula, Pavan; Kim, Yong-Rak; Little, Dallas N; Rushing, John
Abstract: Infrastructure such as roadways, airfield pavements, and railways are primarily subjected to cyclic loading conditions. Subgrade soils for such infrastructure systems are often stabilized to meet and improve mechanical properties with the goal of achieving acceptable performance over the life of pavement or rail system under cyclic loading. This requires understanding the behavior of stabilized soils under cyclic loading as well as monotonic compressive strength as is typically done. This paper discusses a simple and fundamentally sound test method used to investigate the behavior of stabilized soils under cyclic loading. Cylindrical specimens compacted using a Harvard miniature compaction apparatus are subjected to oscillatory torsional loading applied in the strain amplitude sweep mode. To characterize the response of the stabilized soils under cyclic loading, four parameters resulting from the testing were examined: peak shear stress amplitude, dynamic shear modulus, phase angle, and dissipated strain energy. This test method was applied to a simulant soil that was treated using three different additives and cured in two ways. The results of the analysis of the test method using the four parameters showed that the coefficient of variation was in a range of 10–20%, which infers good repeatability. A high sensitivity to the type of stabilizing agents and curing conditions was observed. The energy dissipation response during strain-sweep cyclic loading showed unique time-varying hysteresis loops when different stabilizing agents and curing conditions were used. Furthermore, the method identified two critical strain amplitudes—one indicating the onset of significant nonlinear behavior and the other representing the failure of specimens. Both strain amplitudes were distinctively different from the cases when varying the stabilization methods.